Epistemic Risk - Alves, Eduardo (2025)
The following is a translation of Duncan Pritchard's article Epistemic Risk (2016), in which he argues in favor of a modal account of risk and lays the foundations for an anti-risk epistemology. Pritchard's goal in this article is twofold: First, he argues that his modal account of risk is a natural extension of his modal account of luck, developed in previous writings. Second, by using his modal account of risk to achieve an anti-risk epistemology, Pritchard argues that this strategy has advantages for answering some of the worries raised by his original anti-luck account. Namely, a gap in his anti-risk epistemology can be easily bridged by his anti-risk epistemology, and there are stronger motivations to adopt the latter than the former.